2004
DOI: 10.1002/hyp.1453
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the movement of coarse gravel using implanted motion‐sensing radio transmitters

Abstract: Abstract:Motion-sensing radio transmitters were implanted in cobbles (72-92 mm diameter) and placed in a stream in southwest Idaho for 43 days during a snowmelt period. The radios transmit different pulse rates depending on whether the rocks are at rest or in motion. Every 30 s, a datalogger samples the receiver and records the pulse rate of the transmitters. Such information can be used to assess numerous properties of particle transport that are beyond the capabilities of conventional tracking methods. Concl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 14 publications
0
53
0
1
Order By: Relevance
“…In fact, previous studies demonstrated that the handling of sediments causes the disruption of surface structures (i.e., clusters) and can increase sediment transport by decreasing the critical shear stress Oldmeadow and Church, 2006). A second advantage is the possibility of monitoring a wide range of grain sizes, whereas other tracing techniques [such as motion-sensing radio transmitters (McNamara and Borden, 2004) or passive integrated transponder tags (Lamarre et al, 2005)] are adoptable only for coarse sediments. Finally, the analysis can rely on a large number of particles, because hundreds or thousands of particles (approximately from 1000 to 3000 in our study) are included in a small area (e.g., 0.8× 0.8 m).…”
Section: Advantages and Drawbacks Of The Methodsmentioning
confidence: 98%
“…In fact, previous studies demonstrated that the handling of sediments causes the disruption of surface structures (i.e., clusters) and can increase sediment transport by decreasing the critical shear stress Oldmeadow and Church, 2006). A second advantage is the possibility of monitoring a wide range of grain sizes, whereas other tracing techniques [such as motion-sensing radio transmitters (McNamara and Borden, 2004) or passive integrated transponder tags (Lamarre et al, 2005)] are adoptable only for coarse sediments. Finally, the analysis can rely on a large number of particles, because hundreds or thousands of particles (approximately from 1000 to 3000 in our study) are included in a small area (e.g., 0.8× 0.8 m).…”
Section: Advantages and Drawbacks Of The Methodsmentioning
confidence: 98%
“…The size and travel distance of mobilized grains can be estimated using painted pebbles (Leopold et al, 1966;Billi, 1988;Petit et al, 2005a), tracers containing iron or magnets (Hassan, 1990;Schmidt and Ergenzinger, 1992;Gintz et al, 1996;Ferguson et al, 2002), PIT-tag (Lamarre et al, 2005;Rollet et al, 2008) or active (radio) tracers (Ergenzinger et al, 1989;Busskamp and Hasholt, 1996;MacNamara and Borden, 2004). These methods evaluate bedload mobility over a relatively short timescale.…”
Section: Introductionmentioning
confidence: 99%
“…Elles ont été obtenues au moyen de trappes à charge de fond automatiques, de type Birkbeck. L'utilisation de radio émetteurs pour le traçage des particules sur une rivière à forte pente (2,6 %) de l'Idaho a permis d'analyser finement les périodes de déplacement et de repos de la charge grossière et le couplage de ces informations avec les hydrogrammes de crues a montré des * c compris entre 0,027 et 0,063 (McNamara et Borden, 2004). proposent une gamme comprise entre 0,030 et 0,086 d'après la compilation de 80 années d'étude de transport solide dans les rivières à charge graveleuse.…”
Section: Discussionunclassified